Discussion of An Empirical Study of Accounting Methods and Stock Prices - Neter, John (Journal of Accounting Research, 1969)
Dr. Mlynarczyk is to be complimented on a most interesting study. The effect of accounting information on stock prices is an important and relevant topic. The study was well thought through. The choices of industry and accounting effect appear to be good ones, and the statistical -methodology utilized is appropriate for a cross-section study. I particularly like the author's investigation of the appropriateness of the model through an examination of residuals, checking for possible presence of correlated errors, unequal variances, and lack of normality. Too often, investigators will employ a model and draw inferences from it without even examining the appropriateness of the model. Mlynarczyk is also to be commended for attempting to see whether the magnitude of the accounting effect is in agreement with theoretical expectations. Too often in regression studies, investigators are content to note the presence of a significant regression coefficient without investigating further whether its magnitude is reasonable. Since a discussant should not only note the strong points of a study but also criticize weak points, let me now turn to some criticisms. First I will consider criticisms involving the methodology of this study, and then turn to criticisms on the inferences drawn. The methodology employed uses stock prices at one point in time during the year. However, accounting effects on stock prices presumably take place over a period of time, for instance, as information spreads and is acted upon. Also, the use of data at one point during the year may make it more difficult to disentangle the accounting method effect since random effects are emphasized. This brings up one minor point. If the different companies do not have identical fiscal periods, the effect of the length of the time interval be-